Model-based thermodynamic analysis of supercritical water gasification of oil-containing wastewater. (15th December 2021) - Xu, Jialing; Peng, Zhiyong; Rong, Siqi; Jin, Hui; Guo, Liejin; Zhang, Xiang; Zhou, Teng
Highlights: Increasing temperature and decreasing oil concentration promote hydrogen production. Qualitative and quantitative analysis of char formation is explicitly performed. SCWG reaction can be self-sustainable by adding a small amount of O2 . Abstract: Supercritical water gasification (SCWG) is a promising technology for oil-containing wastewater treatment. In this work, a non-stoichiometric two-phase (i.e., supercritical and solid phases) model is established for the thermodynamic analysis of SCWG of oil-containing wastewater. Within the model, the compositions of gaseous and solid products are calculated by minimizing the Gibbs free energy of the whole system. Peng-Robinson equation is employed to help predict the chemical potentials of gases accurately. The introduced model is first validated to fit experimental data well. Afterwards, the model is used to investigate the effects of various operating conditions on product compositions. A high temperature and a low oil concentration promote hydrogen production, instead of methane production. Additionally, it is found whether and how much char is formed greatly depends on the temperature and elemental compositions in the input stream. Moreover, the reaction heat duty and high heating value of gaseous products are analyzed. SCWG process is endothermic with a low oil concentration and can be energetically self-sustainable via adding O2 at an expense of lowering the heating value of gaseous products. The obtained results can provide useful insights on designing optimal SCWG process for treating oil-containing wastewater.